2020
DOI: 10.3390/v12090934
|View full text |Cite
|
Sign up to set email alerts
|

The Yin and the Yang of Treatment for Chronic Hepatitis B—When to Start, When to Stop Nucleos(t)ide Analogue Therapy

Abstract: Over 257 million individuals worldwide are chronically infected with the Hepatitis B Virus (HBV). Nucleos(t)ide analogues (NAs) are the first-line treatment option for most patients. Entecavir (ETV) and tenofovir disoproxil fumarate (TDF) are both potent, safe antiviral agents, have a high barrier to resistance, and are now off patent. They effectively suppress HBV replication to reduce the risk of cirrhosis, liver failure, and hepatocellular carcinoma (HCC). Treatment is continued long-term in most patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 82 publications
(97 reference statements)
0
19
0
Order By: Relevance
“…Meanwhile, patients with cirrhosis were suggested to continue NA therapy and cessation might be associated with high risks. 3,4,14,18 In the cohort of Van Hees et al 10 18% of included patients were diagnosed with cirrhosis, the median consolidation therapy period was Although a consensus that HBeAg positive CHB patients need longer consolidation therapy before NA cessation has been reached, the duration of consolidation treatment is still controversial. Kuo et al 19 and Lee et al 13 preferred consolidation of 1 year or more, Jun et al 20 and Dai et al 11 found that a consolidation period of at least 18 months was a predictor for SVR after cessation, and Chi et al 12 concluded that prolongation of consolidation therapy beyond 3 years decreased the risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, patients with cirrhosis were suggested to continue NA therapy and cessation might be associated with high risks. 3,4,14,18 In the cohort of Van Hees et al 10 18% of included patients were diagnosed with cirrhosis, the median consolidation therapy period was Although a consensus that HBeAg positive CHB patients need longer consolidation therapy before NA cessation has been reached, the duration of consolidation treatment is still controversial. Kuo et al 19 and Lee et al 13 preferred consolidation of 1 year or more, Jun et al 20 and Dai et al 11 found that a consolidation period of at least 18 months was a predictor for SVR after cessation, and Chi et al 12 concluded that prolongation of consolidation therapy beyond 3 years decreased the risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Our cohort also evaluated similar conclusions. Meanwhile, patients with cirrhosis were suggested to continue NA therapy and cessation might be associated with high risks 3,4,14,18 . In the cohort of Van Hees et al 10 .…”
Section: Discussionmentioning
confidence: 99%
“…TDF and TAF are also extensively and efficaciously used as pre-exposure prophylaxis (PrEP) against HIV infection in people at risk of acquiring this infection [ 57 , 58 , 59 , 60 , 61 ]. The current first line therapies for chronic HBV infection also includes TDF and TAF, which have proven to be well-tolerated and also highly effective in preventing liver fibrosis progression [ 62 , 63 , 64 ]. Further, tenofovir has been proposed to reduce the risk of herpes simplex virus 1 and 2 (HSV-1, HSV-2) infections, although studies have shown conflicting results [ 65 , 66 , 67 , 68 ].…”
Section: Introductionmentioning
confidence: 99%
“…HBV chronic carriers are at high risk of developing severe liver diseases, such as cirrhosis and cancer, culminating in 887,000 HBV-associated deaths annually. Conventional nucleoside analogue therapy suppresses replication without fully clearing the virus; therefore, the therapy is lifelong and can pose a financial burden [ 4 , 5 , 6 , 7 , 8 ]. Despite the global impact of HBV and advances in therapeutics [ 9 , 10 , 11 , 12 , 13 , 14 ], a cure for this chronic infection is yet to be developed.…”
Section: Introductionmentioning
confidence: 99%